Comunicação mediada pelo computador: blog - gênero discursivo emergente - Ormundo, Joana (Cadernos de Linguagem e Sociedade, 2010)
This paper examines the language of the blogs from the point of view of Critical Discourse Analysis as it is conceived by Norman Fairclough. The main aim is to analyse discourse practices in the on-line context. The interactive process and the constitution of discourse community in blogs will be examined according to the genre analysis approach developed by Bakhtin (1997) and the concept of discourse community developed by Swales(1990).